Mladinska dela štirih literarnih ustvarjalcev, članov mariborske peterice - Haramija, Dragica (Slavia Centralis, 2020)
THE LITERARY OPUS OF FOUR CHILDREN’S LITERATURE WRITERS, THE MEMBERS OF THE MARIBOR FIVEThe article looks at the works of children’s literature in the literary opus of four authors, members of the group known as the Maribor Five, France Forstnerič, Marijan Kramberger, Andrej Brvar and Tone Partljič. One of the basic features in the writing for young readers of all three authors is an autobiographic element, directing them to motifs from childhood. The main character is the child/author/ narrator at a younger age, the exception being certain works by Partljič, which can be classified as biographical and adventure prose. Three authors have also received awards for their works for young readers.
Keywords: children’s literature; group Maribor Five; France Forstnerič; Marijan Kramberger; Andrej Brvar; Tone Partljič